Trade Wars and Trade Deals : Estimated Effects using a Multi-Sector Model - Caceres, Carlos (IMF Working Papers; Working Paper ;, 2019)
This paper studies the potential long-term effects of three illustrative scenarios using a multi-sector computable general equilibrium (CGE) trade model calibrated to 165 countries. The first scenario estimates effects from potential U.S. auto tariffs. The second analyzes a 'transactional deal' between the U.S. and China to close their bilateral deficit. The third, in the absence of such a deal, considers a potential escalation in bilateral tariffs between the two countries. Some common features emerge across all three scenarios: the overall effects on GDP tend to be relatively small albeit negative in most cases, including for the U.S. However, sectoral disruptions and positive and negative spillovers to highly exposed 'by-stander' economies can be large. There is also heterogeneity at the subnational level in the U.S. -- richer states tend to benefit from certain scenarios. We discuss how estimated impacts depend on the extent to which the U.S. is able to re-shore production in protected sectors. These results can usefully complement estimates obtained through macroeconomic models that are better suited to capture dynamic effects, such as those stemming from trade policy uncertainty. More generally, our results both underscore the value of adhering to the existing levels of liberalization, and highlight the risks associated with a fragmentation or even a complete breakdown of the trading system.